The Epistemic Transformation Demanded by the Post-Pandemic period: Reflections from the Faculty of Philosophy and Letters of The National University of Costa Rica - Barrantes Montero, Luis Guillermo (2022)
A calm reflection is presented and in a rather familiar tone from the perspective of axiological epistemology about the teachings that the Zeitgeistor spirit of times tries to instill in the academic community as well in the whole society as a result of the over two years of the Covid-19 pandemic suffered by most of humankind. Such teachings not only can but must set the course for the construction and promotion of new and reinvented forms of common sense. For this aim, the proposal of the epistemic transformation both from the merely informative as well as from the functional components of knowledge to the axiological dimension is shown as attention to an urgent claim of the contemporary human beings urged to articulate their double access to knowledge, the one that is related to their subsistence and the one that allows them to situate themselves in the very depths of existence to integrate everything that converges in them.